EFEKTIFITAS LAYANAN KONSELING PERORANGAN YANG DILAKUKAN GURU BK DALAM PENCAPAIAN KEMANDIRIAN PESERTA DIDIK DI SMP N 30 PADANG - Yopirizal, Yopirizal; Kasih, Fitria; Wira Nita, Rahma (Bimbingan dan Konseling, 2013)
This research is motivated by the implementation of individual counseling services conducted counselor teacher. Based on the initial survey found students still problem and has not appointed its independence after doing individual counseling with counselor teacher. This study aimed to look at how the effectiveness of individual counseling services are performed in the attainment of independence counselor teacher learners, the research problem definition, namely :1) Effectiveness of individual counseling services are conducted on understanding and self-acceptance in a positive and dynamic, 2) Effectiveness of individual counseling services towards understanding and acceptance objectively and dynamic environment, 3) Effectiveness of individual counseling services to the appropriate decision-making, 4) Effectiveness of individual counseling services for self-direction in accordance with the decision taken, 5) Effectiveness of individual counseling services for optimal self-realization. This research is a descriptive study. Sampling was done by using purposive sampling. As the sample of students who have done individual counseling with counselor teachers. Data were collected through filling questionnaires by learners. The data were processed by using percentages. The findings of the study revealed that the effectiveness of individual counseling services are performed in the attainment of independence counselor teacher learners effective.